1998
DOI: 10.1002/ana.410430409
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis: In situ evidence for antibody‐ and complement‐mediated demyelination

Abstract: We describe a case of multiple sclerosis characterized by deposition of immunoglobulin and complement in the areas of active demyelination. This was particularly evident for the C9neo antigen, which is a marker for the activated lytic complement complex and was exclusively deposited in the areas of active myelin destruction. In addition, macrophages in the lesions contained degradation products that were immunoreactive for myelin antigens, immunoglobulins, and C9neo antigen. Destruction of myelin sheaths was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
223
0
9

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(242 citation statements)
references
References 25 publications
(1 reference statement)
10
223
0
9
Order By: Relevance
“…This hypothesis has been supported by the presence of oligoclonal IgG bands (OCB) [2] in the cerebrospinal fluid (CSF) of MS patients and antibody and complement depositions in MS lesions [3]. Additionally, clonally restricted Ig genes suggesting the presence of an antigendriven immune response have been found in MS lesion tissue [4].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis has been supported by the presence of oligoclonal IgG bands (OCB) [2] in the cerebrospinal fluid (CSF) of MS patients and antibody and complement depositions in MS lesions [3]. Additionally, clonally restricted Ig genes suggesting the presence of an antigendriven immune response have been found in MS lesion tissue [4].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the activated terminal lytic complex of complement as identified by antibody to the cryptic C9 neo antigen was found exclusively co-deposited with IgG in areas of ongoing myelin breakdown (23,24). Additionally, C9 neo and IgG are found in macrophages containing myelin debris in active MS lesions, providing evidence of a direct role for complement in myelin breakdown (23). This notion is further supported by the presence of membrane attack complex-enriched membrane vesicles in MS CSF (25).…”
Section: Antibody In Msmentioning
confidence: 91%
“…Applying multifactorial cluster analysis to very early MS lesions, Gay et al (22) suggested that the primary lesion in MS is mediated by activated microglia and macrophages containing membrane-bound fixed complexes of both IgG and complement C3d. More recently, the activated terminal lytic complex of complement as identified by antibody to the cryptic C9 neo antigen was found exclusively co-deposited with IgG in areas of ongoing myelin breakdown (23,24). Additionally, C9 neo and IgG are found in macrophages containing myelin debris in active MS lesions, providing evidence of a direct role for complement in myelin breakdown (23).…”
Section: Antibody In Msmentioning
confidence: 99%
“…This latter property is a recognized pathogenic factor in a wide spectrum of chronic inflammatory diseases, including rheumatoid arthritis (13), glomerulonephritis (14), atherosclerosis (15), asthma (16,17), and multiple sclerosis (18). Thus, it is not surprising that evidence for complement-mediated disease pathogenesis has centered primarily on dysfunctional immunity caused by the absence, alteration, or overactivity of complement proteins (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%